The competitiveness of Romagna wineries. An exploratory analysis of the impact of different strategic approaches on business performance - Lorenzo Bandieri; Alessandra Castellini (Wine Economics and Policy, 2023)
This paper proposes an exploratory study of the competitiveness of Romagna wineries. A double approach has been adopted to analyse it, as both Porter’s Theory of Competitive Advantage and Barney’s Resource-based Theory have been considered. The final purposes are to uncover which categories of resources and capabilities are related to firm performance and to investigate the main strategic orientations of the most successful Romagna wineries. To conduct the research, an online questionnaire was sent to 115 wineries located in the Romagna territory, achieving a response rate of about 24.35%. According to the preliminary results, it has been found that the most successful wineries in this area do not follow a cost leadership strategy, while they perform a differentiation strategy. These firms put a lot of effort into building a reputation in the market. On the other hand, managerial and technological capabilities seem to be not positively related to firm performance, while marketing capabilities exert a stronger impact. This study would give an input to the strategic and managerial studies in the wine business sector, and adopt an innovative theoretical approach in the analysis of competitive advantage. Moreover, this work focuses on the Romagna territory, fulfilling the need for research that considers the local wine industry and its competitiveness, to open the way to further studies.